Imidazo[1, 2-b]pyridazines targeting Toxoplasma gondii calcium-dependent protein kinase 1 decrease the parasite burden in mice with acute toxoplasmosis. Issue 7 (June 2018) - Moine, Espérance; Moiré, Nathalie; Dimier-Poisson, Isabelle; Brunet, Kévin; Couet, William; Colas, Cyril; Van Langendonck, Nathalie; Enguehard-Gueiffier, Cécile; Gueiffier, Alain; Héraut, Bruno; Denevault-Sabourin, Caroline; Debierre-Grockiego, Françoise
Graphical abstract: Highlights: Imidazo[1, 2- b ]pyridazine salts inhibit Toxoplasma gondii CDPK1 and tachyzoites. Pharmacokinetic analyses demonstrate good brain penetration. Imidazo[1, 2- b ]pyridazine salts show strong efficacy in vivo on acute toxoplasmosis. Abstract: The current therapeutic arsenal for toxoplasmosis is restricted to drugs non-specific to the parasite which cause important side effects. Development of more efficient and specific anti- Toxoplasma compounds is urgently needed. Imidazo[1, 2- b ]pyridazines designed to inhibit the calcium-dependent protein kinase 1 of Toxoplasma gondii ( Tg CDPK1) and effective against tachyzoite growth in vitro at submicromolar ranges were modified into hydrochloride salts to be administered in vivo in a mouse model of acute toxoplasmosis. All protonated imidazo[1, 2- b ]pyridazine salts (SP230, SP231 and SP232) maintained their activity on Tg CDPK1 and T. gondii tachyzoites. Rat and mouse liver microsomes were used to predict half-life and intrinsic clearance, and the pharmacokinetic profile of the most rapidly degraded imidazo[1, 2 b ]pyridazine salt (SP230) was determined in serum, brain and lungs of mice after a single administration of 50 mg/kg. Compounds were then tested in vivo in a murine model of acute toxoplasmosis. Mice infected with tachyzoites of the ME49 strain of T. gondii were treated for 4, 7 or 8 days with 25 or 50 mg/kg/day of SP230, SP231 or SP232. The parasite burdens were strongly diminished (>90% reduction under some conditions) in the spleen and the lungs of mice treated with imidazo[1, 2- b ]pyridazine salts compared with untreated mice, without the need for pre-treatment. Moreover, no increases in the levels of hepatic and renal toxicity markers were observed, demonstrating no significant signs of short-term toxicity. To conclude, imidazo[1, 2- b ]pyridazine salts have strong efficacy in vivo on acute toxoplasmosis and should be further tested in a model of mouse congenital toxoplasmosis.